LITERATURE REVIEW: NEUROLOGICAL ASPECT OF CORONAVIRUS DISEASE 2019 (COVID-19): PART III. NEUROLOGICAL COMPLICATIONS - Arthur H.P. Mawuntu; Devina C Mastari; Albertus T. Lapian; Agnes K.S. Hermawan; Mieke A.H.N. Kembuan (Jurnal Sinaps, 2021)
Coronavirus disease 2019 (COVID-19) not only has common manifestations of COVID-19 infection arefever, cough, malaise, and respiratory problems, but also neurological manifestations such as decreasedconsciousness, headache, anosmia, stroke, seizures, polyneuropathy, and myopathy. These neurologicalmanifestations support other serious neurological complications found in patients with COVID-19 andsimilar coronaviruss, severe acute respiratory syndrome (SARS-CoV-1) and Middle East respiratorysyndrome (MRS-CoV). This paper discusses the neurological aspects related to COVID-19 infection,neurological complication and high-risk neurology patients. Issues discussed in other parts werepathomechanism, clinical manifestations, and drug interactions Understanding this may help manage thepatient